PENGEMBANGAN MEDIA KOMIK BERBASIS DIGITAL DENGAN PENDEKATAN DEEP LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Muhammad Fathul Fuadi; Panca Dewi Purwati; Agus Yuwono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Instructional media play a vital role in assisting teachers to facilitate effective learning and achieve educational goals. At SDIT Ibnu Yunsi Kota Binjai, however, the existing teaching materials are considered insufficiently engaging, which negatively affects the learning process and contributes to low student performance. Preliminary investigations reveal that students’ academic abilities remain relatively low. This study aims to design and develop digital comic-based learning media that integrates a deep learning approach to enhance students’ academic achievement, particularly in the Indonesian language subject. The research adopts a development methodology based on the Borg and Gall model. Data were collected through interviews, questionnaires, and classroom observations. The participants involved were fourth-grade students from SDIT Ibnu Yunsi Kota Binjai, along with the digital media and instructional content created. The media was evaluated by both media and subject matter experts, who rated it as highly accessible and user-friendly. Validation and field-testing results demonstrated that the media significantly improved students’ learning outcomes, with an effectiveness rate reaching 90%. Therefore, the study concludes that the deep learning-oriented digital comic media developed is highly suitable as a teaching aid for Indonesian language instruction at the elementary school level.